Criticality safety analysis for eccentric loading of fuel assemblies in spent nuclear fuel cask - Seok Geun Cho; Keon Il Cha; Kyoon Ho Cha (Nuclear Engineering and Technology)
Eccentric fuel loading is one of the studies performed in a spent nuclear fuel criticality safety analysis. Several studies have been performed to investigate the effect of increasing reactivity on eccentric loading and random displacement in spent nuclear fuel pools; However, studies within spent nuclear fuel casks have not been performed. Therefore, this study investigates the effects of eccentric loading and random displacement of fuel assemblies on the reactivity in the spent nuclear fuel cask. The spent nuclear fuel cask and PLUS7 fuel are modeled using the MCNP code to investigate these effects. The result indicates that in eccentric cases, the k-effective values exceed those observed in the normal case. Also, several random displacement cases show k-effective values that exceed the normal case. These results differ from previous studies on eccentric loading in the spent fuel pool. It supports the necessity of considering both eccentric loading and random displacement in the criticality safety analysis in spent nuclear fuel cask. The increase in reactivity due to eccentric loading and random displacement of fuel assemblies within casks might be considered in criticality safety analysis and regarded as an uncertainty.